Supervising the Undergraduate Engineering Team Project- Sharing of Experience - Zainal Abidin, Azizan (2008)
The curriculum structure of Universiti Teknologi PETRONAS, Malaysia requires students in the third year (first semester) of a four year undergraduate engineering program to undergo a semester of Engineering Team Project, a three-credit hour course. Students registered in the various disciplines, namely Electrical and Electronics, Mechanical, Civil, and Chemical is assigned to groups to work and deliver a working prototype at the end of thirteen weeks. Based on the topics provided by the author to two groups, each comprising of six students, work their way through the thirteen weeks of a fourteen-week semester, deliberate and overcome the challenges and difficulties together to achieve the objective of the project. Managing the Engineering Team Project requires strict discipline on both parties; students and supervisor alike. A systematic method of assessment is also in place to ensure that work at all stages; initial, in-progress and final, are all carefully recorded and evaluated. A proposal, progress report, a final report, and a short group viva are the tools used to measure students’ abilities in achieving the learning outcomes of the course. The written work is submitted together with a demonstration of the working prototype. At the end of twelve weeks, each group is required to do a viva, where evaluation is done by a panel of two internal examiners. A convincing presentation, accompanied by a comprehensive poster and a working prototype may qualify a team to an exhibition where the project will be displayed and the team gets the opportunity to compete with others in an Engineering Design Exhibition at the university level. What does it take to create good teamwork in completing and producing a deliverable worth exhibiting and good enough to earn some form of recognition? What does it take to supervise such team projects? How does a lecturer with non-engineering background take up such a supervision job? The objective of this paper is to share supervision experience of such Engineering Team Projects and to reveal the students’ feedback upon completion of their work.